A concise history of the Qing Dynasty - Dai, Yi 1926- (Silkwood Press, 2011)
The most complete and authoritative look at the last feudal monarchy in China's long history, A Concise History of the Qing Dynasty (4-volume set) details the birth of what would become modern-day China. Covering the fall of the Manchurians, these 4 volumes offer a comprehensive look at the last dynasty in China. Under Qing rule, China saw art and culture flourish even while the nation faced invasion by hostile foreign powers and oppression under the subsequent unequal treaties. A Concise History of the Qing Dynasty (4-volume set) is a landmark work on Chinese history by China's leading expert